2017
DOI: 10.1016/j.memsci.2016.12.054
|View full text |Cite
|
Sign up to set email alerts
|

The effect of restriction membranes on mass transfer in an electrodialysis with filtration membrane process

Abstract: In an electrodialysis with filtration membrane (EDFM) separation process, a pair of restriction membranes is used to prevent leakage of molecules into the electrode solution. Driven by the electrical potential gradient, ions transport across these membranes in different directions, resulting in concentration changes in the feed and permeate compartments respectively. However, the effects of these restriction membranes have not been systemically studied to date. In the present work, the performance of a non-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
5
1
Order By: Relevance
“…The BSA flux obtained in repeat experiments using the CEM restriction membranes was highly variable. Contrary to our prior work [53], there also appeared to be no increase in this flux relative to the use of a PAm restriction membrane. The pH changes observed in our earlier work were much less significant, due to the use of an alternate buffer system.…”
Section: Reduction Of Protein Loss Due To Foulingcontrasting
confidence: 99%
See 2 more Smart Citations
“…The BSA flux obtained in repeat experiments using the CEM restriction membranes was highly variable. Contrary to our prior work [53], there also appeared to be no increase in this flux relative to the use of a PAm restriction membrane. The pH changes observed in our earlier work were much less significant, due to the use of an alternate buffer system.…”
Section: Reduction Of Protein Loss Due To Foulingcontrasting
confidence: 99%
“…Only around half of this absorbed lactoferrin can be desorbed when using a salty water wash. While not discussed in our prior work [53], the use of ion exchange membranes in place of the neutral PAm, is likely to also cause the onset of greater water splitting, which in turn will result in significantly greater energy demand and higher electro-osmotic flows of water. Indeed, the PAm membranes results in less water transfer than when ion exchange membranes are used ( Table 2).…”
Section: Reduction Of Protein Loss Due To Foulingmentioning
confidence: 87%
See 1 more Smart Citation
“…48 It can also valorize desalination brines to produce acids and bases using bipolar membrane. 21 ED can concentrate (i) precious metals such as lithium 49 and cadmium 50 ions, and (ii) nutrient ions and organic compounds such as citric acid, 51 protein 52 and glycine, 53 from impaired water.…”
Section: Conventional Electrodialysis (Ed)mentioning
confidence: 99%
“…It has been observed that electrochemical techniques represent low cost and high selectivity along with the fruitless recovery of treated metals for a recycled, high volume of sludge formation [9,14]. Likewise, the ion exchange and membrane filtration processes are restricted due to their selectivity, high operational cost and maintenance issues [20]. However, the adsorption process, by all accounts, has shown unrivaled outcomes due to its minimal effort, high effectiveness and selectivity [21].…”
Section: Introductionmentioning
confidence: 99%